IMPLIKASI DARI MEDIA SOSIAL KEMODERASI SOSIAL DALAM PEMBENTUKAN KARAKTER RELIGIUS TERHADAP PESERTA DIDIK - Ghozali (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2025)
Social media has become an integral part of students' lives and has a significant influence on social interaction patterns and the formation of religious character. This study aims to analyze the implications of social media on social moderation in the formation of students' religious character. The research method used is library research with a contextual analysis approach. (Contextual analysis) is used to understand the phenomenon of social media by considering the social, cultural, educational, and religious backgrounds of students as described in various scientific sources. Data collection was carried out through searching and selecting library sources in the form of books, national and international journal articles, previous research results, and educational policy documents relevant to the themes of social media, social moderation, and religious character education. The collected data was analyzed through the stages of theme classification, data reduction, contextual interpretation, and critical conclusion drawing. The results of the study show that social media has dual implications in shaping the religious character of students. Social media can serve as a means of internalizing moderate, tolerant, and inclusive religious values, but it also has the potential to give rise to intolerant and exclusive attitudes if not balanced with adequate digital literacy and guidance. Therefore, strengthening media literacy and integrating social moderation values into religious character education are strategic steps that need to be implemented in the educational environment.